The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/836790
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Genetic Polymorphisms and Human Immunodeficiency Virus Infection in Lipid Metabolism

Abstract: Dyslipidemia has been frequently observed among individuals infected with human immunodeficiency virus type 1 (HIV-1), and factors related to HIV-1, the host, and antiretroviral therapy (ART) are involved in this phenomenon. This study reviews the roles of genetic polymorphisms, HIV-1 infection, and highly active antiretroviral therapy (HAART) in lipid metabolism. Lipid abnormalities can vary according to the HAART regimen, such as those with protease inhibitors (PIs). However, genetic factors may also be invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 157 publications
0
11
0
Order By: Relevance
“…It has been suggested that host genetic polymorphisms influence the risk of developing numerous diseases in HIV-infected people. [16][17][18] Estrogene hormone is well known to play an essential role in the growth and development during childhood and estrogen receptors (ERs) mediate much estrogen action.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that host genetic polymorphisms influence the risk of developing numerous diseases in HIV-infected people. [16][17][18] Estrogene hormone is well known to play an essential role in the growth and development during childhood and estrogen receptors (ERs) mediate much estrogen action.…”
Section: Discussionmentioning
confidence: 99%
“…The main genes studied are those that encode proteins, receptors, and enzymes related to lipid metabolism and regulation. Polymorphisms in LDLR, apoE, apo B, apo A-I, apo C-III, apo A-V, PCSK9, CETP, and LP genes have been associated with changes in lipid profile [45]. Regarding the LDLR gene, over 1,288 different variants have been implicated in the etiology of dslipidemia [46].…”
Section: Discussionmentioning
confidence: 99%
“…Because gene polymorphisms cause dyslipidemia, they should be investigated in these patients to identify individuals with an increased risk of developing dyslipidemia when on HAART, especially those containing PIs. This knowledge could guide individualized treatment decisions and lead to new therapeutic targets for the treatment of dyslipidemia [45].…”
Section: Discussionmentioning
confidence: 99%
“…The degree of inflammatory and metabolic response to ischemic stroke may be variable and the extent variability in genes coding for proteins of pathways involved in the inflammation (Waterer and Wunderink 2003) and in the metabolism (de Almeida et al 2013), considered the main pathophysiologic pathways of ischemic stroke, limits the generalization of previous results to the Brazilian population, considered one of the most genetically heterogeneous worldwide, as result of a great miscegenation (Pena et al 2011;Brazil 2013b).…”
Section: Introductionmentioning
confidence: 99%